Three-year mortality in 30-day survivors of critical care with acute kidney injury: data from the prospective observational FINNAKI study - Henriikka Mildh; Ville Pettilä; Anna-Maija Korhonen; Sari Karlsson; Tero Ala-Kokko; Matti Reinikainen; Suvi T. Vaara; and the FINNAKI Study Group (My University, 2022)
Background
The role of an episode of acute kidney injury (AKI) in long-term mortality among initial survivors of critical illness is controversial. We aimed to determine whether AKI is independently associated with decreased survival at 3 years among 30-day survivors of intensive care.
Results
We included 2336 30-day survivors of intensive care enrolled in the FINNAKI study conducted in seventeen medical–surgical ICUs in Finland during a 5-month period in 2011–2012. The incidence of AKI, defined by the Kidney Disease: Improving Global Outcomes criteria, was 34.6%, and 192 (8.3%) commenced RRT. The 3-year mortality among AKI patients was 23.5% (95% CI 20.6–26.4%) compared to 18.9% (17.0–20.9%) of patients without AKI, p = 0.01. However, after adjustments using Cox proportional hazards regression, AKI was not associated with decreased 3-year survival (HR 1.05; CI 95% 0.86–1.27), whereas advanced age, poor pre-morbid functional performance, and presence of several comorbidities were. Additionally, we matched AKI patients to non-AKI patients 1:1 according to age, gender, presence of severe sepsis, and a propensity score to develop AKI. In the well-balanced matched cohort, 3-year mortality among AKI patients was 136 of 662 (20.5%; 17.5–23.6%) and among matched non-AKI patients 143 of 662 (21.6%; 18.5–24.7%), p = 0.687. Neither AKI nor RRT was associated with decreased survival at 3 years in the sensitivity analyses that excluded patients (1) with chronic kidney disease, (2) with AKI not commenced renal replacement therapy (RRT), and (3) with estimated pre-admission creatinine, chronic kidney disease, or AKI stage 1.
Conclusion
AKI was not an independent risk factor for 3-year mortality among 30-day survivors. Increased 3-year mortality among patients with AKI who survive critical illness may not be related to AKI per se, but rather to advanced age and pre-existing comorbidities.